Development of an Indirect ELISA Based on a Recombinant Chimeric Protein for the Detection of Antibodies against Bovine Babesiosis - Jaramillo Ortiz, Jose Manuel (2018)
The current method for Babesia spp. serodiagnosis based on a crude merozoite antigen is a complex and time-consuming procedure. An indirect enzyme-linked immunosorbent assay (iELISA) based on a recombinant multi-antigen of Babesia bovis (rMABbO) was developed for detection of antibodies in bovines suspected of infection with this parasite. The multi-antigen comprises gene fragments of three previously characterized B. bovis antigens: MSA-2c, RAP-1 and the Heat Shock protein 20 that are well-conserved among geographically distant strains. The cutoff value for the new rMABbo-iELISA was determined using 75 known—positive and 300 known—negative bovine sera previously tested for antibodies to B. bovis by the gold-standard ELISA which uses a merozoite lysate. A cutoff value of ≥35% was determined in these samples by receiver operator characteristic (ROC) curve analysis, showing a sensitivity of 95.9% and a specificity of 94.3%. The rMABbo-iELISA was further tested in a blind trial using an additional set of 263 field bovine sera from enzootic and tick-free regions of Argentina. Results showed a good agreement with the gold standard test with a Cohen’s kappa value of 0.76. Finally, the prevalence of bovine babesiosis in different tick enzootic regions of Argentina was analyzed where seropositivity values among 68–80% were obtained. A certain level of cross reaction was observed when samples from B. bigemina infected cattle were analyzed with the new test, which can be attributed to shared epitopes between 2 of the 3 antigens. This new rMABbo-iELISA could be considered a simpler alternative to detect anti Babesia spp. antibodies and appears to be well suited to perform epidemiological surveys at the herd level in regions where ticks are present